“Paths of Monarchical Mercy”: Judicial Powers of Monarch and Constitutional Reform of 1906 - S. V. Kulikov (Научный диалог, 2024)
This article presents a novel examination of a pivotal aspect of the creation of the Fundamental State Laws enacted on April 23, 1906, specifically addressing the question of the Emperor’s judicial powers. It is noted that previous iterations of the Fundamental State Laws (1832) did not delineate these powers, despite the acknowledgment of the judicial supremacy of monarchs in constitutional monarchies, particularly their right to grant pardons. The article analyzes different definitions of the Tsar’s judicial powers as outlined in three drafts of new Fundamental Laws prepared for Nicholas II in late 1905. Among these drafts, the proposal by P. A. Kharitonov emerged as the leading version. In both the draft from the State Chancellery and that of Professor O. O. Eikhelman, the judicial powers of the autocrat were framed similarly to those characteristic of constitutional monarchies at the beginning of the 20th century. In March 1906, the State Chancellery’s draft was reviewed by the Council of Ministers, chaired by Count S. Yu. Witte. With his support, conservative amendments were introduced to the draft — abolishing the nonremovability of judges established by the Judicial Statutes of 1864, preserving the Tsar’s direct involvement in administering justice, and affirming his right to dispense justice. It is demonstrated that during a Special Meeting in April 1906, liberal officials opposed these amendments, while Nicholas II sided with their critics. In the final version of the Fundamental Laws, the judicial powers of the Tsar largely conformed to European constitutionalism of the early 20th century.